Discovering computers 2018 digital technology, data, and devices - Vermaat, Misty E.; Sebok, Susan L.; Freund, Steven M.; Campbell, Jennifer T.; Frydenberg, Mark (Mark E.) (Cencage Learning, 2018)
Teach students to maximize their use of mobile devices, make the most of online tools for collaboration and communication, and fully utilize today's Internet capabilities with the latest edition of DISCOVERING COMPUTERS 2018. Introductory computing students see how technology skills assist in employment and advancing their careers. This edition highlights today's most current technology trends and developments. Timely coverage now emphasizes web development, how to create a strong web presence, and take full advantage of latest Windows 10. The authors provide helpful suggestions for hands-on exercises, small group activities, and discussion topics that allow students to apply and demonstrate their understanding of each module. Self-assessments open each module and enable learners to focus their study and learn more in less time. DISCOVERING COMPUTERS presents the key content that students need for success, using an inviting approach that ensures understanding